CityLoops - Demonstration action evaluation plans ... - Hansen, Jens Ørding; Hellemans, Adriaan; van Laar, Sanne; Kristensen, Tor Gausemel; Yates, Erika; Jessen, Laura Heron; Bech, Line; Fritzen, Caroline Juel; Mikkelsen, Josephine; Malk, Vuokko; Järvinen, Johanna; Soininen, Hanna; et al. (Zenodo, 2023)
This file collects the evaluation plans for the circular economy (CE) demonstration actions of seven European cities participating in the Horizon 2020 project CityLoops (GA no. 821033). The evaluation plans offer detailed, practical examples of how CE indicator methodologies can be tailored to a variety of real-world contexts. In particular, the plans illustrate how some of the key indicators from the dataset “CityLoops circular economy indicator set (complete)”, also accessible in Zenodo, can be applied in practice. The plans were completed by the CityLoops demonstration cities in 2022. ... : Edited by Nordland Research Institute ...